2019
DOI: 10.17268/sci.agropecu.2019.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Cultural, biological and chemical control of Moniliophthora roreri and Phytophthora spp IN Theobroma cacao ‘CCN-51’

Abstract: El objetivo de este estudio fue evaluar diferentes métodos de control de enfermedades de la mazorca de Theobroma cacao 'CCN-51' en Santo Domingo de los Tsáchilas, Ecuador. Los tratamientos fueron una mezcla de dos pesticidas químicos (Clorotalonil y Pyraclostrobin) y uno biológico (Bacillus subtilis) con y sin fertilizante. En total se evaluaron 16 tratamientos con 3 repeticiones, instalados en una plantación comercial de cacao 'CCN-51' y bajo un Diseño de Bloques Completos al Azar (DBCA). Los resultados mostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
6
Order By: Relevance
“…La producción de cacao es muy importante en países tropicales como el Ecuador, pero persisten problemas sanitarios que limitan el aumento de la productividad y por tanto causan un daño a la economía de los pequeños productores cacaoteros (Anzules et al, 2019). De los tres problemas detectados en las mazorcas de cacao CCN-51, el "cherelle wilt" fue el de mayor incidencia, con valores prácticamente similares para las dos localidades estudiadas (21%) y más altos que los reportados para "moniliasis" y "pudrición parda".…”
Section: Resultados Y Discusiónunclassified
“…La producción de cacao es muy importante en países tropicales como el Ecuador, pero persisten problemas sanitarios que limitan el aumento de la productividad y por tanto causan un daño a la economía de los pequeños productores cacaoteros (Anzules et al, 2019). De los tres problemas detectados en las mazorcas de cacao CCN-51, el "cherelle wilt" fue el de mayor incidencia, con valores prácticamente similares para las dos localidades estudiadas (21%) y más altos que los reportados para "moniliasis" y "pudrición parda".…”
Section: Resultados Y Discusiónunclassified
“…These results demonstrated that, for the control of the pathogens in cacao pods, the cultural labors were important, but when it was complemented with other control methods (biological or chemical), the results were better and allowed to obtein the highest rates of economic return (Jáuregui, 2001). In a similar work carried out in the Ecuadorian town of Puerto Limon, it was found that in a treatment where various components were also combined [Cultural Labor + Chlorothalonil (1 kg ha -1 ) (every 15 days) + Pyraclostrobin (0.5 kg ha -1 ) (every 90 days) + Fertilizer (0.4 kg plant -1 ) + Fertilizer (2 kg plant -1 )], the results showed that it was the one that allowed the highest net income per ha (Anzules et al, 2019). In other study carried out in Manabi (Ecuador), the percentage of healthy pods increased due to the use of chemical fungicides (Arroyave, 2007), but the number of pods and the yield were not directly related and the highest yield of dry cocoa corresponded to T9, a biological control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is only with good agricultural practices that chemical and biological interventions are cost-effective, because cultural methods alone are inadequate to control FPR (Bateman et al, 2005). Several studies report the use of fungicides as a tactic within a FPR disease management in cacao farms (Anzules et al, 2019;Bailey et al, 2018;Bateman et al, 2005;Krauss et al, 2010;Terrero Yépez et al, 2018;Torres De La Cruz et al, 2013). In this context, the lack of cacao resistant clones (Yamashita & Fraaije, 2018;Zhao et al, 2019), high morphological and molecular diversity of pathogen (Maridueña-Zavala et al, 2016), and the disease development due to climatic variables (Leandro-Muñoz et al, 2017) make it necessary to develop programmed applications of fungicides.…”
Section: Introductionmentioning
confidence: 99%